2001
DOI: 10.4315/0362-028x-64.9.1309
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Escherichia coli O157:H7 and Salmonella Enteritidis in Cow Manure Composting

Abstract: Application of cow manure and composted manure in agricultural practice could potentially cause contamination of foodstuffs with pathogenic bacteria such as Salmonella Enteritidis and Escherichia coli O157:H7. In this study, rifampicin-resistant (RifR) E. coli O157:H7 and Salmonella Enteritidis at a level of 7 log CFU/g of raw compost feed were used to determine the effect of a bench-scale composting system on their survival. RifR E. coli O157:H7 was not detected after 72 h of composting at 45 degrees C, and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 12 publications
4
72
0
2
Order By: Relevance
“…Concern has been raised by the EU Scientific Committee on Food on the possible contamination of fruit and vegetables by sewage sludges, animal manures or irrigation waters (SCF, 2002). Indeed, they can provide pathogenic microorganisms such as bacteria pathogenic to humans (Strauch, 1991) (Lung et al, 2001;Droffner and Brinton, 1995;Vuorinen and Saharinen, 1997;Tiquia et al, 1998). This could be less efficient in eliminating Clostridium botulinum (Bohnel and Lube, 2000).…”
Section: Pathogenic Microorganismsmentioning
confidence: 99%
“…Concern has been raised by the EU Scientific Committee on Food on the possible contamination of fruit and vegetables by sewage sludges, animal manures or irrigation waters (SCF, 2002). Indeed, they can provide pathogenic microorganisms such as bacteria pathogenic to humans (Strauch, 1991) (Lung et al, 2001;Droffner and Brinton, 1995;Vuorinen and Saharinen, 1997;Tiquia et al, 1998). This could be less efficient in eliminating Clostridium botulinum (Bohnel and Lube, 2000).…”
Section: Pathogenic Microorganismsmentioning
confidence: 99%
“…Paniel et al (2010) demonstrated that faecal Enterococcus was not observed during the stabilization phase. Palmisano and Barlaz (1996); Lung et al (2001);Tønner-Klank et al (2007) showed that proper composting can kill many human pathogens in different types of compost, and the temperatures achieved during the treatment (50-70°C) are able to kill the enteric pathogens. This stage of the process is defined as disinfection or sanitization.…”
Section: Coliforms Versus Time Of Co-composting Processmentioning
confidence: 99%
“…The heap of organic waste undergoes microbial degradation that converts organic waste into compost. During composting, organic material passes through the thermophilic phase (45-65°C) that kills numerous pathogenic microorganisms due to release of CO 2 , water and heat (Lung et al 2001;Alidadi et al 2005;Mehta et al 2014;Soobhany et al 2017). Several physio-chemical parameters affect the composting process such as temperature, moisture, pH, particle size, aeration and electrical conductivity (Li et al 2013;Juárez et al 2015;Onwosi et al 2017).…”
Section: Traditional Organic Compostingmentioning
confidence: 99%